Development of Teaching Learning Method With the Problem Solving to Improve Soft Skill - Sarjito Surya (International Conference on Education and Language (ICEL), 2013)
Based on teaching experience and observations made by the lecturer during lecturing, some of the problems are student’s interest and motivation are decrease and it effected on the passing grade students, the understanding of the students about the subject have to be increased, the soft skill for problem solving is less and the last is the students sometimes afraid to say and share their opinion in the class. The purpose on this paper is how to develop teaching learning method with problem solving to improve soft skill of the students are alsoeffecting the passing rates in the class.